The effect of ellagic acid on intra-abdominal adhesions caused by gallstones - (:unkn) unknown (Lippincott Williams and Wilkins, 2021)
Background: Adhesion formation after peritoneal surgery is the main cause of postoperative bowel obstruction, infertility, and chronic pelvic pain. In this study, we evaluated the effect of oral ellagic acid on intra-abdominal adhesions caused by gallstones in rats. Materials and Methods: Forty-one Wistar-albino rats were used. Gallstones were dropped to the right lower quadrant of the abdomen to create adhesions. They were divided into 4 groups; sham-operated, intraperitoneal gallstone, oral ellagic acid (control), and intraperitoneal gallstone+oral ellagic acid. On the postoperative 10th day, relaparotomy was performed, adhesions were evaluated according to four different macroscopic adhesion score systems and adhesion-bearing tissues were examined histopathologically. Samples were graded for inflammation, vascularization, and fibrosis. Results: We found that oral administration of ellagic acid lowered all macroscopic adhesion scores. There were significant differences between groups of sham and gallstone; control and gallstone; control and gallstone+oral ellagic acid (P < 0.05). Conclusion: The ellagic acid administered orally at a dose of 100 mg/ kg/d significantly inhibited intra-abdominal adhesion formation and no adverse effects were seen between treatments. Copyright © 2021 Wolters Kluwer Health, Inc. All rights reserved.
Keywords: Adhesions related to gallstones; Ellagic acid; Intra-abdominal adhesions; Rat model